Metrics Analysis in Object Oriented and Aspect Oriented Programming - Gulia, Preeti; Khari, Manju; Patel, Shrikant (Recent Patents on Engineering, 2019)
Background: Object oriented programming (OOP) is a programming paradigm that has been used for several years by the software engineering community. The best practice of OOP was gathered and they are known as Design Patterns. They provide guidelines for developing flexible software applications. Recent studies claim that some patterns have limitations and their implementations could be improved. Researchers claim that Aspect Oriented Programming (AOP) is a paradigm that provides features to overcome the limitations of OOP and patterns. However, even with the good results achieved using AOP, it is possible to cause side effects in code. We revised all patents relating to aspect oriented programming of applicability. This paper tries to implement a subset of the patterns with AOP and identify merits and demerits in comparison with the traditional OOP implementations. In another term if a method which is called several time in different class so we use to write code on both classes (if we don’t want to overload it) and manually write code of function call after those methods which we want to execute. Methods: Aspect-Oriented Programming entails breaking down program logic into distinct parts called so-called concerns. The functions that span multiple points of an application are called cross-cutting concerns and these cross-cutting concerns are conceptually separate from the application's business logic. There are various common good examples of aspects like logging, auditing, declarative transactions, security, and caching, etc. Results: after the implement AOP concept with OOPs, the response time is reduce and throughput rate is increases. And the development of program is become more easy and reliable. Conclusion: so those method which is called several time in a program execution these type of method must be written in AOP so it is triggered automatically when the pointcode if occurred.
Keywords: crosscutting concern